Insolvency Prospects Among Small-and-Medium-Sized Enterprises in Advanced Economies : Assessment and Policy Options - Diez, Federico (Staff Discussion Notes; Staff Discussion Notes, 2021)
The COVID-19 pandemic has increased insolvency risks, especially among small and medium enterprises (SMEs), which are vastly overrepresented in hard-hit sectors. Without government intervention, even firms that are viable a priori could end up being liquidated-particularly in sectors characterized by labor-intensive technologies, threatening both macroeconomic and social stability. This staff discussion note assesses the impact of the pandemic on SME insolvency risks and policy options to address them. It quantifies the impact of weaker aggregate demand, changes in sectoral consumption patterns, and lockdowns on firm balance sheets and estimates the impact of a range of policy options, for a large sample of SMEs in (mostly) advanced economies.